Upaya Meningkatkan Kemampuan Motorik Halus Pada Anak Usia 5-6 Tahun Melalui Metode Mewarnai Gambar di TK Anugerah Soe - Otce Arman Sunbanu (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to determine efforts to improve the fine motor skills of children aged 5-6 years through the method of coloring pictures. This research uses a classroom action research approach carried out in two cycles. Each cycle goes through four stages, namely: planning, implementation, observation and reflection. The subjects of this research were Anugerah Soe Kindergarten with 27 children aged 4-6 years, consisting of 8 girls and 19 boys. Data is collected through observation, documentation and performance. Data analysis uses qualitative descriptive methods. The results of the research show that coloring activities are very appropriate for developing the fine motor skills of kindergarten children because through coloring activities children learn about initial writing skills, namely the ability to hold coloring tools, move the wrist and hand-eye coordination which is very useful for the next level of education. Therefore, implementing coloring activities for kindergarten children is considered very appropriate.